Shorter Maintenance Therapy in Childhood Acute Lymphoblastic Leukemia: The Experience of the Prospective, Randomized Brazilian GBTLI ALL-93 Protocol - Brandalise, Silvia R.; Viana, Marcos B.; Pinheiro, Vitória R. P.; Mendonça, Núbia; Lopes, Luiz F.; Pereira, Waldir V.; Lee, Maria L. M.; Pontes, Elitânia M.; Zouain-Figueiredo, Gláucia P.; Azevedo, Alita C. A. C.; Pimentel, Nilma; Fernandes, Maria Z.; et al. (Frontiers in Pediatrics, 2016)
Maintenance therapy is an important phase of the childhood ALL treatment, requiring 2-year long therapy adherence of the patients and families. Weekly methotrexate (MTX) with daily 6-mercaptopurine (6MP) constitutes the backbone of maintenance therapy. Reduction in the maintenance therapy could overweight problems related with poverty of children with ALL living in Limited-Income countries (LIC). Objective: To compare, prospectively, the EFS rates of children with ALL treated according to two maintenance regimens: 18 vs 24 months duration. Materials and Methods: From October 1993 to September 1999, 867 consecutive untreated ALL patients < 18 years of age, were treated according to the Brazilian Cooperative Group for Childhood ALL Treatment (GBTLI) ALL-93 protocol. Risk classification was based exclusively on patient’s age and leucocyte count (NCI Risk Group) and clinical extra medullary involvement of the disease. Data was analyzed by the intention-to-treat approach. Results: Fourteen patients (1.6%) were excluded: wrong diagnosis (n=7) and previous corticosteroid (n=7). Of the 853 eligible patients, 421 were randomly allocated, at study enrollment, to receive 18-month (group 1) and 432 to receive 24-month (group 2) maintenance therapy. Complete remission rate was achieved in 96% of the patients (817/853). Twenty-eight patients (3.4%) died during the induction phase. Thirty-four patients (4.0%) were lost to follow-up. The overall EFS was 66.1% ± 1.7% at 15 years. No difference was seen according to maintenance: EFS15y was 65.8% ± 2.3% (group 1) and 66.3% ± 2.3% (group 2; p=0.79). No difference between regimens was detected after stratifying the analyses according to factors associated with adverse prognosis in this study (age group <1 year or >10 years and high WBC at diagnosis). Overall death in remission rate was 6.85% (56 patients). Deaths during maintenance were 13 in group 1 and 12 in group 2, all due to infection. Over 15 years of follow-up, two patients both from Group 2 presented a second malignancy (Hodgkin’s disease and thyroid carcinoma) after 8.3 and 11 years off therapy, respectively. Conclusion: Six-month reduction of maintenance therapy in ALL children treated according to the GBTLI ALL-93 protocol, provided the same overall outcome as 2-year duration regimen.